PENERAPAN KECAKAPAN HIDUP (LIFE SKILL) PADA MATA PELAJARAN BATIK JUMPUT DI SEKOLAH DASAR - Yuyarti Yuyarti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
This research is the class research act that used the cycle of planning, actuating, observation and reflection. The background of the research problem with the application of life skill to the batik jumput subject where has been done yet in the elementary school, the quality of learning in the elementary school still low, the learning tend to teoritical and lack of relation to the factual world and the student less aplicatif. While the aim of this research are (1) to make the model structure learning with the application of life skill to the batik jumput subject in the elementary school (2) to increase the student learning achievement (3) to develop the student activity or life skill and (4) analize the teacher skill in the maintain the learning process. The technique of collecting data in this research used the test sheet i.e to reveal the student achievement in learning process. Observation sheet to analize the activity and the ability of teacher in the maintain learbing activity. The result that get in the application of skill life to the batik jumput subject can increase the student learning achievement, the student and teacher competent in maintain the learning process. The student have desire to develop what they have been practice to be provision next if they don`t continue the education to the high label. With the simple work is the provision of life skill i.e skill self, social skill, academic and vocational is the prove that has been produce the product of batik jumput from the natural colour. According to the result of research it is advised to the teacher in elementary school in the batik jumput learning with the material immerse batik ikat it is hope to find the concepts that they learn according to the local domain so the learning more meaningful.